c-Src Kinase Inhibition Reduces Arrhythmia Inducibility and Connexin43 Dysregulation after Myocardial Infarction - Rutledge, Cody A. (2014)
OBJECTIVES: The aim of this study was to evaluate the role of c-Src inhibition on connexin43 (Cx43) regulation in a mouse model of myocardial infarction (MI). BACKGROUND: MI is associated with decreased expression of Cx43, the principal gap junction protein responsible for propagating current in ventricles. Activated c-Src has been linked to Cx43 dysregulation. METHODS: MI was induced in 12-week-old mice by coronary artery occlusion. MI mice were treated with c-Src inhibitors (PP1 or AZD0530), PP3 (an inactive analogue of PP1), or saline. Treated hearts were compared to sham mice by echocardiography, optical mapping, telemetry ECG monitoring, and inducibility studies. Tissues were collected for immunoblotting, quantitative PCR, and immunohistochemistry. RESULTS: Active c-Src was elevated in PP3-treated MI mice compared to sham at the scar border (280%, p=0.003) and distal ventricle (346%, p=0.013). PP1 treatment restored active c-Src to sham levels at the scar border (86%, p=0.95) and distal ventricle (94%, p=1.0). PP1 raised Cx43 expression by 69% in the scar border (p=0.048) and by 73% in distal ventricle (p=0.043) compared to PP3 mice. PP1-treated mice had restored conduction velocity at the scar border (PP3: 32 cm/s, PP1: 41 cm/s, p < 0.05) and lower arrhythmic inducibility (PP3: 71%, PP1: 35%, p < 0.05) than PP3 mice. PP1 did not change infarct size, ECG pattern, or cardiac function. AZD0530 treatment demonstrated restoration of Cx43 comparable to PP1. CONCLUSIONS: c-Src inhibition improved Cx43 levels and conduction velocity and lowered arrhythmia inducibility after MI, suggesting a new approach for arrhythmia reduction following MI.